2012
DOI: 10.1093/icvts/ivs367
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barre syndrome after coronary artery bypass surgery

Abstract: A case of the Guillain-Barré syndrome occurring after otherwise uneventful cardiac surgery using cardiopulmonary bypass is presented. Though the Guillain-Barré syndrome has been reported after surgical procedures, there are very few case reports after cardiopulmonary bypass surgery in the literature. The exact pathophysiological cause of the syndrome is still unknown. However, the most widely accepted hypothesis is that the syndrome is the result of an immune-mediated process. Cardiac surgery may be a trigger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…During the past decades, there have been a number of reports presenting GBS following different types of surgery (3)(4)(5)(6)(7)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), but only 5 of the cases (3-7) developed the complication 8 to 22 days after spine surgery ( Table 4). The 4 post-spinal-surgery GBS we observed were out of a total of 7770 cases; the incidence of GBS after spine surgery is 1 per 2,000 (4/7770).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decades, there have been a number of reports presenting GBS following different types of surgery (3)(4)(5)(6)(7)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), but only 5 of the cases (3-7) developed the complication 8 to 22 days after spine surgery ( Table 4). The 4 post-spinal-surgery GBS we observed were out of a total of 7770 cases; the incidence of GBS after spine surgery is 1 per 2,000 (4/7770).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the original articles are case reports (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Since this condition is rare, it is possible that patients would be M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 misdiagnosed and subsequently treated incorrectly.…”
Section: Introductionmentioning
confidence: 99%
“…Cases of GBS have been described after cranial, vascular and facial surgery [10][11][12][13][14][15][16][17][18]. A retrospective assessment of admitted GBS patients demonstrated a statistically significant increased risk for developing GBS after surgery compared to the general population (RR 13.1; p < 0.0001) [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this analysis of 63 patients, six received either orthopedic or gastrointestinal surgery within six weeks prior to symptomatic presentation. Similarly, various authors have reported cases of post-operative GBS after cardiac [10,15], bariatric [17] and neurosurgical procedures [19,20]. Though the underlying pathophysiology of post-operative GBS has not yet been determined, Gensicke et al in their analysis suggested that physiological stressors associated with surgery, in addition to compromised immunological function post-operatively may serve as a nidus for infection, with subsequent humoral responses [14].…”
Section: Introductionmentioning
confidence: 99%
“…The risk for GBS after surgery is 4.1% cases per 100 000 operations. 1 Very few cases have been reported in the literature after CABG [2][3][4][5]. Table 1summarizes these published case reports.…”
mentioning
confidence: 99%